VdP5CDH is involved in melanin formation, stress resistance and play a regulatory role in virulence of Verticillium dahliae - Sun, Wanqing; Zhao, Lihong; Zhou, Jinglong; Feng, Hongjie; Zhang, Yalin; Feng, Zili; Zhu, Heqin; Wei, Feng (Frontiers in Microbiology, 2024)
Introduction Verticillium dahliae, a soil-borne fungal pathogen, can cause cotton Verticillium wilt. In this study, VdP5CDH, the member of the ALDH_F4-17 family of carboxylate dehydrogenases, was identified in the genome of V. dahliae and investigated function in regulating virulence by generating gene deletion mutants and complementary mutants. Methods Homologous recombination method was used to construct mutants, transcriptome sequencing revealed gene-related metabolic pathways, and disease degree of cotton was observed through pathogen infection experiments. Results The conidial surface of VdP5CDH deletion strains was dented and shriveled, and the number of conidial spores increased. Compared with the wild-type (WT), the mycelial diameter of deletion mutants increased by 10.59%-11.16%, the mycelial growth showed irregular branching patterns, and misaligned arrangement. Although capable of penetrating cellophane, deletion mutants were unable to produce melanin. VdP5CDH was mainly associated with glucose metabolism, nitrogen metabolism, ABC transporter activity as well as various amino acid metabolic processes. After gene knockout, raffinose and pectin were used as the main carbon sources to promote the growth of strains and the growth rate of deletion strains in the medium containing raffinose was higher than that of WT. Consequently, the deletion mutant strains decreased utilization efficiency with which they utilized various nitrogen sources. The deletion mutants maintain responsiveness to osmotic stress and oxidative stress stimuli. Additionally, compared to WT strains, the deletion mutant strains exhibited differences in culture temperature tolerance, UV exposure response, and fungicide sensitivity. After cotton was infected with deletion strains conidial suspension, its disease index increased dramatically, while it gradually decreased after spraying with 2 mM glutamate in batches. With the increase of spraying times, the effect was more significant, and the disease index decreased by 18.95%-19.66% at 26 dpi. Discussion These results indicated that VdP5CDH regulates the pathogenicity of fungi and controls mycelia growth, melanin formation, conidia morphology, abiotic stress resistance, and the expression of infecting structure-related genes.